Synthesis and affinities of C3-symmetric thioglycoside-containing trimannosides. (14th August 2015) - Bi, Jingjing; Zhao, Chuanfang; Cui, Wei; Zhang, Chaoli; Shan, Qiuli; Du, Yuguo
Abstract: Thioglycoside-containing trimannose analogs were designed and prepared to mimic the natural N-glycan core trisaccharide α-d -Man-(1→3)-[α-d -Man-(1→6)]-d -Man. (1→6)- S -Linked trimannoside1 and its trivalent cluster2 were synthesized in 11 and 15 steps, respectively, taking advantages of the armed mannopyranosyl trichloroacetimidate as glycosyl donor. Hemagglutination inhibition of the two new thiomannotriose analogs was preliminarily examined. Comparing to the parent trimannoside α-d -Man-(1→3)-[α-d -Man-(1→6)]-d -Man-OMe, the cluster mannotrioside2 presented a comparable binding affinity to Con A, while the monomer 6- S -trimannoside1 exhibited a slightly lower inhibition ability. Graphical abstract: Highlights: The monomer and trivalent of (1→6)- S -trimannoside are synthesized convergently. Compared to O-trimannose, 6- S -trimannose exhibits only slightly lower inhibition. The cluster compound shows a comparable binding affinity to Con A. Modeling suggests a very little binding effect on trimannose O- and S -glycoside.